(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The digitalization, automation, and greater use of technology that define the contemporarybanking system have greatly enhanced the effectiveness and accessibility of financial transactions.Customers are more satisfied since they may use this system to access banking services and goodswhenever and wherever they choose. Charges for banking services have decreased as a consequence ofcontemporary banking systems’ success in cutting down on banks’ overhead. The development of thecurrent banking system has also allowed for the development of novel goods and services that aredesigned to fulfill the individual requirements of their clientele. Financial services that can be accessedvia a mobile device, such as mobile banking, internet banking, digital wallets, and other safe paymentmethods, are included here.